Stay Of Proceedings Pending Arbitration: Protecting The Interests Of Third-Parties To Arbitration In Nigeria - Alatise, Taofeeq N. (Journal of Sustainable Development Law and Policy, 2025)
Courts have the power to stay proceedings pending arbitration. In Nigeria, the enabling statute regulating commercial arbitration is the Arbitration and Conciliation Act of 1988. Sections 4 and 5 of the Act contain two similar but conflicting provisions regulating the stay of proceedings. These sections of the law are a product of a common ground found in two different legislative texts. While section 4 leveraged on the provision of Uncitral Model Law on Arbitration, section 5 is influenced by Arbitration Act of 1914. This dichotomy between the histories of the two sections partly accounts for the controversies and difficulties in the interpretation and application by courts and scholars. This article examines the scope of sections 4 and 5 of the Act by identifying the real object of the law and the flaws in its current interpretation. The article considers the American experience, especially, the attitude of courts in granting a stay of proceedings and whether a stay can be granted in a suit against a non-party to the arbitration agreement. Unlike arbitration laws in the United States, one key gap in Nigerian arbitration law is its failure to contemplate stay of proceedings in a suit against a non-party to an arbitration agreement. In addition to identifying the need for urgent legal reforms that accommodate third-party stay pending arbitration, this article recommends that Nigerian courts, like their counterparts in developed jurisdictions, should adopt a more proactive approach by evolving innovative ways in deciding suits involving third parties to arbitration agreement and stay proceedings pending arbitration in appropriate cases to prevent parties from avoiding arbitration by suing a third-party, in line with the global best practices.